Perencanaan dan Perancangan Rumah Sakit Ibu dan Anak Deltamas Dengan Pendekatan Behavior Architecture - Retno Fitri Astuti; Ari Wicaksono (DPPM Universitas Pelita Bangsa, 2022)
Bekasi Regency is one of the industrial areas in West Java. So there are various kinds of factories that produce various kinds of products. With so many factories in Bekasi Regency, it will lead to higher levels of urbanization or population movement from rural to urban areas higher in order to earn a living and change fate. From the data obtained, from BPS data for Bekasi Regency in 2015 the population was 72,911 people, in 2015 in 2016 the population was 92,595, in 2017 the number was 95,316, in 2018 the number population of 100,714, and in 2019 the population of 103,535. And along the development of time, the need for housing facilities to support life those in urban areas will increase. And of course, of course the immigrants and the natives will start building a family and settle in Bekasi Regency. So that The need for health facilities will definitely increase, for example, hospitals. In In this case, from the data obtained, the number of RSIA facilities in Bekasi Regency is still low minimal, especially in Central Cikarang District, which does not have the facilities at all Hospital and Mother and Child Hospital. That's why it's necessary planning for the procurement of RSIA in Central Cikarang District with the behavior architecture. This behavior architecture serves as a bridge for change the mood of building users when they are active in it. This concept can be implemented to building elements such as site concept, interior, material nor color. By analyzing the behavior, especially the mother and child, then will create an atmosphere of fun play space inside and outside the building so that healing process can be faster. As well as the use of open areas as healing garden at the hospital is also a solution to be applied in the district Bekasi, if you look at the behavioral architecture. With the addition of this green space in addition to to reduce pollution and excessive heat can also have an effect on the process patient healing. Keywords : Bekasi, Central Cikarang, Industry, Hospital, Mother And Child Hospital, Behavior Architecture